Gene therapy for hereditary hearing loss by SLC26A4 mutations in mice reveals distinct functional roles of pendrin in normal hearing - Mina Kim; Sung Huhn Kim; Nari Ryu; Ji-Hyun Ma; Ye‐Ri Kim; Jinsei Jung; Chuan‐Jen Hsu; Jae Young Choi; Kyu-Yup Lee; Philine Wangemann; Jinwoong Bok; Un‐Kyung Kim (2019)
Rationale: Mutations of SLC26A4 that abrogate pendrin, expressed in endolymphatic sac, cochlea and vestibule, are known to cause autosomal recessive sensorineural hearing loss with enlargement of the membranous labyrinth.This is the first study to demonstrate the feasibility of gene therapy for pendrin-related hearing loss.Methods: We used a recombinant viral vector to transfect Slc26a4 cDNA into embryonic day 12.5 otocysts of pendrin-deficient knock-out (Slc26a4 ∆/∆ ) and pendrin-deficient knock-in (Slc26a4 tm1Dontuh/tm1Dontuh ) mice.Results: Local gene-delivery resulted in spatially and temporally limited pendrin expression, prevented enlargement, failed to restore vestibular function, but succeeded in the restoration of hearing.Restored hearing phenotypes included normal hearing as well as sudden, fluctuating, and progressive hearing loss. Conclusion:Our study illustrates the feasibility of gene therapy for pendrin-related hearing loss, suggests differences in the requirement of pendrin between the cochlea and the vestibular labyrinth, and documents that insufficient pendrin expression during late embryonal and early postnatal development of the inner ear can cause sudden, fluctuating and progressive hearing loss without obligatory enlargement of the membranous labyrinth.